Protective Effect of Boerhavia diffusa in Attenuating Pro-inflammatory Cytokines and Inhibition of Activated NF-κB-TNF-α-Nrf2 in Freund’s Adjuvant-induced Rheumatoid Arthritis - Karwasra, Ritu; Sharma, Shivkant; Sharma, Nitin; Khanna, Kushagra (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Boerhavia diffusa is widely used in Asian and African countries in the treatment of inflammatory disorders in adjunct with other herbal formulations. The current research work was devised with an aim to examine the protective effect of hydroalcoholic root extract of Boerhavia diffusa in rheumatoid arthritis. Materials and Methods: Hydroalcoholic extract of plant at varying doses and reference drug (indomethacin 3mg/kg), were administered daily for 21 days. The parameters such as joint diameter, level of antioxidant (GSH) and pro-oxidant (MDA) markers and histolopathological evaluation were performed. Immunohistochemical analysis was carried out to evaluate the effect of Boerhavia diffusa on pro-inflammatory (IL-1), anti-inflammatory (IL-10), pro-inflammatory TNF-α and its receptor, TNF-R1, angiogenesis (VEGF), Nrf-2 and NF-κB. Results: Findings of study discovered that there is dose dependent significant (p<0.05) reduction in inflammation by varying doses of Boerhavia diffusa along with the reduction (p<0.01) in levels of oxidant stress markers. Notable decline in inflammation and joint dysfunction was found in Boerhavia diffusa 200 mg/kg dose with significance of p<0.001. Conclusion: We concluded that the tuberous roots of Boerhavia diffusa show dose dependently attenuate paw edema, inflammation and reversed the bone damage through inhibition of activated pro-inflammatory mediators, Nrf-2 and specifically NF-κB-mediated production of cytokines.
Keywords: Boerhavia diffusa; Rheumatoid Arthritis; NF-κB pathway; Angiogenesis; Inflamation